Response of native versus exotic plant guilds to cattle and elk herbivory in forested rangeland. Issue 1 (20th August 2015) - Pekin, Burak K.; Wisdom, Michael J.; Parks, Catherine G.; Endress, Bryan A.; Naylor, Bridgett J.
Abstract: Questions: Are exotic plant species favoured by non‐native ungulate herbivores and disadvantaged by native herbivores in forested rangelands? Do the impacts of ungulates on exotic vs native plants depend on forest management activities such as prescribed fire and stand thinning? Location: Northeastern Oregon, USA. Methods: We recorded changes in richness and cover of different exotic and native plant life forms in experimental plots that were grazed only by cattle (a non‐native herbivore), only by elk (a native herbivore) or not grazed by any ungulate over a 7‐yr period at both managed (recently burned and thinned) and unmanaged (where no fire and thinning has occurred in >40 yr) forest stands. Results: There was a general decrease in exotic plant species richness and cover across all treatments. However, the decrease in exotic richness, particularly of exotic annual forbs, was slightly lower in plots grazed by elk than in ungrazed plots at managed stands. Managed stands also displayed a larger increase in native annual forb richness and exotic graminoid richness, and a larger decrease in native perennial graminoid cover with cattle grazing than elk grazing. At unmanaged stands, cover of woody native plants such as shrubs, sub‐shrubs and trees as well as native perennial forbs decreased or remained relatively constant with elk grazing while increasing strongly at plots that were ungrazed or grazed by cattle. Conclusions: Cattle and elk have variable effects on different plant guilds at managed vs unmanaged forest stands. Overall, cattle grazing tends to have a larger impact on herbaceous plant guilds at managed stands, while elk grazing tends to have a larger impact on woody plant guilds at unmanaged stands. However, in contrast to findings from other ecosystems, grazing only has a minor impact on exotic plant dynamics in our study area, and cattle grazing does not favour exotic plants any more than grazing by elk or ungulate exclusion. Abstract : We explore the role of cattle and elk grazing in exotic plant invasions. Both ungulates have similar impacts on exotic and native plant dynamics, and the persistence of exotics on the landscape is largely mediated by vegetation succession stage which corresponds to forest management history. Exotics are extirpated as succession progresses following stand thinning and burning regardless of grazing regime.